Picture Fuzzy CEBOM-PROMETHEE Model for Pricing of Cultural Tourism Products - Sui-Zhi Luo; Si-Huan Hu; Qian Li; Jian Wu (IEEE Access)
Cultural tourism products refer to the special tourism products supported by cultural tourism resources and aimed at obtaining cultural impression and increasing intelligence. This study establishes a hybrid multi-criteria decision-making (MCDM) framework to solve the evaluation and pricing issues of cultural tourism products. In the proposed framework, picture fuzzy sets are adopted to thoroughly depict decision-making information with four independent functions. Simultaneously, a novel picture fuzzy numbers cross-entropy-based optimization model (PFN-CEBOM) is proposed to reveal the significance of decision-making attributes. The advanced PFN-CEBOM can get comprehensive criteria weights by covering both objective and subjective weight data in picture fuzzy environments. Then, the traditional preference ranking organization method for enrichment evaluations (PROMETHEE) is modified with picture fuzzy information to get non-compensatory decision-making results. And finally, the proposed method is applied to evaluate and pricing different cultural tourism products in China. Additionally, the availability and superiority of the proposed model are verified through sensitive and comparative analyses. Results evince that the proposed approach is valid for reasonable pricing of cultural tourism products and can serve as a promising instrument for tourism industries.